2011
DOI: 10.5005/jp-journals-10024-1002
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Endodontic Treatment of Dilacerated Canals: A Survey of Diplomates of the American Board of Endodontics

Abstract: Aim To gather data from Diplomates of the American Board of Endodontics regarding treatment of dilacerated canals. Materials and methods A questionnaire addressing definition, endodontic treatment procedures and prognosis was constructed and distributed via e-mail to 708 Diplomates of the American Board of Endodontics. Data from 150 respondents, a 21% response rate, were collected by using a Web-based interface. For statistical analysis, Chi-square tests were used. Results More than 25% of respondents beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In dilacerated teeth it is often difficult to explore and negotiate the canal to its apical foramen; hence the use of scout file is recommended in these kind of cases [7]. In the present cases # 10k file was inserted in watch-winding motion to confirm the canal patency.…”
Section: Various Techniques Used For Managementmentioning
confidence: 82%
“…In dilacerated teeth it is often difficult to explore and negotiate the canal to its apical foramen; hence the use of scout file is recommended in these kind of cases [7]. In the present cases # 10k file was inserted in watch-winding motion to confirm the canal patency.…”
Section: Various Techniques Used For Managementmentioning
confidence: 82%
“…Endodontic treatment of severely curved root canals is complicated by the difficulty of achieving a hermetic seal, as failure to do so can result in treatment failure (7). The present in vitro study evaluated the effect of MC size on the apical seal of severely curved (dilacerated) root canals and showed that an MC size up to #30 did not significantly increase apical microleakage.…”
Section: Discussionmentioning
confidence: 95%
“…In cases where small, flexible spreaders cannot reach to approximately 1 mm of the working length, lateral compaction may not be the technique of choice (7,18). Although the survey of Dastmalchi et al (7) showed that most ABE Diplomates chose thermoplasticized technique as the best method to obturate severely curved canals, lateral compaction was utilized in the present study because of its widespread use (it is the most commonly used technique in Europe and the United States) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distortion can be minimized by positioning the object in the central part of the x-ray beam, using a parallel technique [11]. Measurement of the working length may be much more di cult in curved canals, which makes the measuring di cult [12].…”
Section: Introductionmentioning
confidence: 99%